Effects of added zinc from zinc sulfate or zinc sulfate/zinc oxide combinations on weanling pig growth performance - Woodworth, J.C.; O'Quinn, P.R.; Musser, R.E.; Moser, S.A.; Fakler, T.M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred and sixty early-weaned pigs were fed either a control diet containing no added Zn; diets containing added Zn (100, 200, or 400 ppm) from zinc sulfate or a combination of zinc sulfate and zinc oxide (50:50 ratio); or a diet containing 3,000 ppm of added Zn from zinc oxide. No additive effects on growth performance were observed with combinations of zinc sulfate and zinc oxide. Increasing levels of zinc sulfate or increasing the combination of zinc sulfate and zinc oxide had no effect on growth performance. Average daily gain and ADFI were highest for pigs fed diets containing 3,000 ppm of Zn from zinc oxide, which is similar to results of previous research at Kansas State University. To achieve maximum growth performance, 3,000 ppm of Zn from zinc oxide should be added to diets of weanling pigs.
Keywords: Swine; Early-weaned pigs; Growth; Zinc